2015
DOI: 10.1007/s10144-015-0504-3
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term pattern of population dynamics in the field vole from central Europe: cyclic pattern with amplitude dampening

Abstract: The subject of population cycles is regarded as controversial due to a number of unsettled questions such as whether or not cyclic patterns are governed by the same processes at high and low latitudes in Europe. Recent evidence suggests that the dynamics at high and low latitudes share the common temporal pattern of vole dynamics referred to as collapsing population cycles. Despite concurrent interest, the key contention around the causal mechanisms that drive population cycles remains a hot topic in ecology. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 44 publications
(77 reference statements)
0
14
0
Order By: Relevance
“…Our results showed important changes in the diet composition of the common buzzard in the last 30 years, which were the result of changes in rodent availability, mainly a decrease in the abundance of voles of Microtus genus, and dampening of their population cycles. Such a collapse in vole cycles was reported in many countries [51][52][53][54], including North-Eastern and Western Poland [55], and referred to Microtus arvalis, M. agrestis and M. oeconomus [55,56]. The reasons for this are not fully explained, yet they are usually connected to climatic changes [57,58] (but see Reference [59]).…”
Section: Diet Composition and Changes In Prey Availabilitymentioning
confidence: 96%
“…Our results showed important changes in the diet composition of the common buzzard in the last 30 years, which were the result of changes in rodent availability, mainly a decrease in the abundance of voles of Microtus genus, and dampening of their population cycles. Such a collapse in vole cycles was reported in many countries [51][52][53][54], including North-Eastern and Western Poland [55], and referred to Microtus arvalis, M. agrestis and M. oeconomus [55,56]. The reasons for this are not fully explained, yet they are usually connected to climatic changes [57,58] (but see Reference [59]).…”
Section: Diet Composition and Changes In Prey Availabilitymentioning
confidence: 96%
“…; Gouveia et al . ). General principles of consumer‐resource theory may help predict the effects of long‐term climatic changes on population cycles (O’Connor et al .…”
Section: How Population Cycling Interacts With Global Change Biodivementioning
confidence: 97%
“…For small mammal species, such as voles, climate change has decreased population size during the peaks of the cycle due to changes in winter growth rates (Cornulier et al 2013). Warm winters generate melt-frost events at northern latitudes, which result in less favourable conditions for herbivores accessing their food through the frozen bottom snow layers (Ims et al 2008;Kausrud et al 2008), although these results are not unequivocal (Korpela et al 2013;Gouveia et al 2015). General principles of consumerresource theory may help predict the effects of long-term climatic changes on population cycles (O'Connor et al 2011) and, more generally, food web dynamics (Gilbert et al 2014).…”
Section: Cycle Gain and Lossmentioning
confidence: 99%
“…This is in accordance with some earlier findings (Solonen and Karhunen 2002;Solonen 2004Solonen , 2006. However, there are studies (Tkadlec et al 2006;Hoset et al 2009;Brommer et al 2010;Korpela et al 2013;Gouveia et al 2015) which have shown a positive or a non-significant relationship between a mild winter and vole population size in the following spring. The present results suggest that the discrepancy between the results of some studies may be due to the differences in the thickness of the snow cover between areas or years considered, as well as between the periods of winter time examined.…”
Section: Impacts Of Winter Weather Conditions On the Population Dynammentioning
confidence: 99%